2021
DOI: 10.1002/qre.2851
|View full text |Cite
|
Sign up to set email alerts
|

Directionally sensitive MCUSUM mean charts

Abstract: In the context of a disease outbreak detection, a prime interest is to only detect increases in the process mean. It is thus desirable to have a directionally sensitive multivariate chart that can effectively detect either increases or decreases in the process mean vector. In this paper, with a suitable transformation that truncates multivariate observations either above or below the process mean vector, we propose one‐sided and two one‐sided MCUSUM charts for monitoring the mean of a multivariate normal proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The OWC, OWP, TOWC, and TOWP charts are weighted adaptive extensions of the existing OC, OP, TOC, and TOP charts, respectively, proposed by Haq and Sohrab. 25 Being nonadaptive charts, the existing OC, OP, TOC, and TOP charts are only useful when the mean shift size where a protection is needed is known in advance, as these charts do not provide optimal performances in the detection of a range of the mean shift sizes. To offset this limitation, the OWC, OWP, TOWC, and TOWP charts have been developed in this paper, as they provide uniformly better protection in the detection of a range of mean shift sizes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The OWC, OWP, TOWC, and TOWP charts are weighted adaptive extensions of the existing OC, OP, TOC, and TOP charts, respectively, proposed by Haq and Sohrab. 25 Being nonadaptive charts, the existing OC, OP, TOC, and TOP charts are only useful when the mean shift size where a protection is needed is known in advance, as these charts do not provide optimal performances in the detection of a range of the mean shift sizes. To offset this limitation, the OWC, OWP, TOWC, and TOWP charts have been developed in this paper, as they provide uniformly better protection in the detection of a range of mean shift sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Then, it can be shown that = −1∕2 ( − ) follows a standard multivariate normal distribution when the underlying process is in an in-control state, i.e., ∼  ( , ) when ≤ , where is a zero vector of dimension × 1, and is an identity matrix of dimension × . To construct C and P charts, Haq and Sohrab 25 considered the following transformations on :…”
Section: The Existing Chartsmentioning
confidence: 99%
See 3 more Smart Citations